Peran Komunikasi Interpersonal Kh Ali Maschan Moesa Membangun Jiwa Nasionalisme di Pesantren Luhur Al Husna Surabaya - Hamdan Yuwafik (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2021)
This paper tries to describe the role of Kh's interpersonal communication. Ali Maschan Moesa in building the nationalism of the students of the Surabaya Al-Husna Islamic Boarding School. The following writing is the result of the study (field research) conducted directly in the field, using a qualitative descriptive analysis approach to the role of Kh's interpersonal communication Ali Maschan Moesa in building the nationalism of the students of the Surabaya Al-Husna Islamic Boarding School. The results of the study show the role of Kh's interpersonal communication. Ali Maschan Moesa in building nationalism is dialogue, cultural exchange or knowledge (exchange), and boarding with the Protestant Church Congregation in West Indonesia Surabaya (GPIB). The role of Khalil Maschan Moesal interpersonal communication in building nationalism and tolerance of the Luhur Al-Husna Islamic boarding school students can be said to be successful because they are able to form the aqidah of students properly and correctly, are able to build relationships related to de-radicalization together across religious communities and there is communication with students in the Forum for Harmony of People Religion (FKUB) in maintaining tolerance in Surabaya.